MENENTUKAN INVERS DRAZIN DARI MATRIKS SINGULAR - Khasanah, Lisnilwati; Bambang, Irawanto (MATEMATIKA, 2011)
A singular matrix A with size has a inverse be called Drazin inverse and denoted by . This inverse can be obtained by specifying a generalized Modal matrix and Jordan canonical form of matrix A. Generalized Modal matrix is a matrix where its columns consisting of generalized eigen vectors from the matrix A, while the Jordan canonical form is a matrix which entries on its main diagonal consisting of Jordan block matrix . Next, two matrices were used to determine Drazin inverse of matrix A.